Motivations of Rural Tourism Entrepreneurs: Conceptual Theory Building Using the Qualitative Study Results - Kenebayeva, A.S.; Xiaotian, Zh. (KU Publ., 2022)
Object: This paper aims to investigate entrepreneurial motivations of various categories of rural tourism entrepreneurs, particularly highlighting the differences between Opportunity, Necessity, and Irrational entrepreneurs with a deep focus on commercial, social, irrational, as well as mixed intrinsic motives in start-up initiatives. Methods: This research adopts the qualitative research method. 25 rural tourism entrepreneurs in Central Asia were studied in-depth, using a purposive sampling strategy. Findings: The research revealed a specific category of rural tourism entrepreneurs defined as Irrational Entrepreneurs, which not connect their initiative and activities with an opportunity to gain philanthropic benefits. Irrational Entrepreneurs are characterized by an extremely social dominance degree in their business motivations. Conclusions: For contributing to the conceptual theory building, the “Dominant Motivation Degrees” model is suggested. The model indicates the impact of social and commercial components of intrinsic motives on an integral nature of entrepreneurial motivations.
Ауылдық туризм саласындағы кәсіпкерлердің мотивациялары: сапалық зерттеулердің нәтижелерін қолдана отырып тұжырымдамалық теория құру
Мотивации предпринимателей в области сельского туризма: построение концептуальной теории с использованием результатов качественного исследования
Keywords: entrepreneurial motivations; tourism and hospitality entrepreneurs; rural tourism; qualitative method; entrepreneurship theory; Kazakhstan